Human Resources on Increasing Teacher Performance in Islamic Education Institution - Aminatul Zahroh; Khurotin Anggraeni; Muhamad Faizul H; H. Karim (Indonesia Emerging Literacy Education, 2021)
Education is strategic to increasing human resources quality which is a determinant factor of national development. To achieve education goals, we need human resources. Human resources are a keys factor in an institution. Human resources will support organizations with their creation, talent, creativity, and support. Education plays an important role in increasing human resources. Human resources in education include principle, teachers, staff, and committees. Teacher plays an important role to decided education success to produce quality output. A teacher is the main key to learning success. The teacher is expecting to create learning education interaction and make innovation to learning quality improvement. The purpose of study is to analysis and finding increasing teacher performance through human resources in Islamic education Institution. The research method used descriptive qualitative. The data collecting method uses in-depth interviews, participant observation, and documentation. The result of the study the human resources at Pondok Pesantren Banyumas Jawa Tengah managed is well. The study has proven with planning, recruitment, teacher selection, placement process or orientation, teacher performance assessment, training, carrier development, compensation and allowance, teacher dismissal. Teacher performance is optimal yet, cause many teachers cannot finish their tasks on time, although discipline is a priority. While the implementation of human resources management did well and given an effect on increasing teacher performance. Many resistances increasing teacher performance is prepared lesson plan and learning media maximal yet